Social Acceptance of Green Hydrogen and Wind Energy: an Integrated Model (Andamios, Revista de Investigación Social, 2026)
This article proposes an innovative model that integrates the social acceptance of green hydrogen and wind energy, addressing the complex interactions between these two technologies. Unlike previous studies, which have examined these aspects separately, our approach provides a comprehensive framework that captures the social dynamics and potential tensions when these energies coexist in the same territory. This model serves as a valuable tool for stakeholders in both the public and private sectors seeking to promote the energy transition, as it facilitates stronger territorial governance and more equitable, participatory implementation of sustainable energy projects.
Keywords: social acceptance; green hydrogen; wind energy; energy transition; integrated model